2017
DOI: 10.1037/pas0000445
|View full text |Cite
|
Sign up to set email alerts
|

Are risk assessments racially biased?: Field study of the SAVRY and YLS/CMI in probation.

Abstract: Risk assessment instruments are widely used by juvenile probation officers (JPOs) to make case management decisions; however, few studies have investigated whether these instruments maintain their predictive validity when completed by JPOs in the field. Moreover, the validity of these instruments for use with minority groups has been called into question. This field study examined the predictive validity of both the Structured Assessment of Violence Risk in Youth (SAVRY; n = 383) and the Youth Level of Service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 68 publications
9
45
1
Order By: Relevance
“…Among the evidence contributed here, we offer a study of the SAVRY's predictive ability through AUC calculations. These values are similar to those found in studies from different countries, using both English-speaking and non-English-speaking samples [27,38,44,45], and are similar to meta-analysis data of risk assessment instruments in young offenders [46]. Our results uphold the utility and good functioning of the SAVRY in contexts and languages outside of North America, making it feasible to compare studies regardless of the youths' nationalities.…”
Section: Discussionsupporting
confidence: 86%
“…Among the evidence contributed here, we offer a study of the SAVRY's predictive ability through AUC calculations. These values are similar to those found in studies from different countries, using both English-speaking and non-English-speaking samples [27,38,44,45], and are similar to meta-analysis data of risk assessment instruments in young offenders [46]. Our results uphold the utility and good functioning of the SAVRY in contexts and languages outside of North America, making it feasible to compare studies regardless of the youths' nationalities.…”
Section: Discussionsupporting
confidence: 86%
“…Self-reported violence and offending has significantly less racial disparity than criminal records (Loeber et al, 2015). Indeed, studies have found no significant differences between Black and White youth on items of an SPJ instrument that counts prior illegal acts and conduct as opposed to only what is on one’s official record (e.g., Chapman et al, 2006; Perrault et al, 2017).…”
Section: Risk Instruments Are Not All Created the Samementioning
confidence: 99%
“…1 Eight tested actuarial instruments (C. Campbell et al, 2018; Flores et al, 2016; Lowder et al, 2019; Perrault et al, 2017; Schwalbe et al, 2004, 2007; Skeem & Lowenkamp, 2016), only one of which was a pretrial risk instrument (Cohen & Lowenkamp, 2018), and three tested SPJ instruments (Lowder et al, 2019; Muir et al, 2020; Perrault et al, 2017). Four of the 10 found significant racial differences in predictive accuracy.…”
Section: What Does It Mean For An Instrument To Be Racially Biased?mentioning
confidence: 99%
“…Within risk assessment research, since 2010, there has been a focus on “Field Validity” (previously referred to as “ecological validity”)—or how a risk assessment tool functions in a real world setting (see Perrault et al, ; Singh & Fazel, ). This focuses on how tools are used by clinicians and the predictions made function in real world practice.…”
Section: Introductionmentioning
confidence: 99%
“…It was weakly "predictive" of accidental self-harm and no better than chance at signalling physical ill health. "ecological validity")-or how a risk assessment tool functions in a real world setting (see Perrault et al, 2017;Singh & Fazel, 2010). This focuses on how tools are used by clinicians and the predictions made function in real world practice.…”
mentioning
confidence: 99%